Hubungan Karakteristik Individu Tehadap Pengetahuan Penggunaan Inhaler Pada Pasien Asma Di Klinik Harum Melati Dan RSU Wisma Rini Kabupaten Pringsewu Tahun 2021 - Muhamad Rizky Fadhilah; Retno Ariza Soemarwoto; Fransiska Tarida Yuniar Sinaga; Jordy Oktobiannobel (Medula, 2022)
Asthma according to the Global Initiative for Asthma 2021 (GINA) is a chronic disease that can cause respiratory symptoms and activity restrictions that can be fatal. One of the success factors for asthma therapy is the use of the right inhaler. This study used a cross sectional approach . Based on the chi-square and Spearman analysis, it was found that there was no relationship between gender and age with p values ​​= 0.191 and 0.319 (p>0.05) and there was a relationship between work and education with p values ​​= 0.000 and 0.000 (p = <0, 05). Individual characteristics greatly affect the knowledge of the use of the patient's inhaler. The relationship between individual characteristics based on age and knowledge of inhaler use shows that there is no relationship. The relationship of individual characteristics based on education to knowledge of inhaler use shows that there is a relationship. The relationship of individual characteristics based on occupation to knowledge of inhaler use shows that there is a relationship. There is a relationship between individual characteristics and knowledge of inhaler use on work and education in asthma patients at the fragrant jasmine clinic and Wisma Rini Public Hospital, Pringsewu 2021.